Border Multiplicities: At the Cross-Roads between Improvisation and Regulation in the Andes. Issue 1 (2nd January 2016) - Ødegaard, Cecilie Vindal
ABSTRACT: Focusing on illicit trade between Peru and Bolivia, this article is concerned with border-work as it unfolds at the cross-roads between improvisation and regulation. The argument of the article is two-fold. First, it argues that cross-border trade in this context must be understood as socially and spatially embedded. The trade involves a sense of local autonomy and networks of cooperation and exchange that not only facilitate illicit trade, but also adds legitimacy and value to cross-border trade, despite its illegal dimensions. Second, the article argues that commodity flows in this context actualize questions about what, where and when the border is . Due to the social and spatial embeddedness of cross-border trade and the authorities' difficulties to limit the smuggling, border-work is multiplied, taking place in various sites beyond the delineated border. The article illustrates how the flow of a particular commodity, namely fuel, has resulted in an intensification and multiplication of border-work due to smuggling.